Obesity, Inflammation and Cancer 2013
DOI: 10.1007/978-1-4614-6819-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fats as Mediators of Obesity, Inflammation, and Colon Cancer

Abstract: Obesity and associated low-grade infl ammation are clearly risk factors for development of diabetes, cardiovascular disease, and cancer; however, the mechanisms and pathways by which obesity and infl ammation lead to these disorders are not clearly defi ned. Since obesity is largely determined by levels of energy expenditure as well as quantities and composition of consumed nutrients, especially fats and carbohydrates, the question exists as to whether obesity and/or dietary components contribute directly to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 191 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…Apart from complement, fatty acids are involved in immunological processes via direct activation of immune cells and release of pro-inflammatory mediators (59). Whereas saturated fatty acids contribute to promoting inflammation, unsaturated fatty acids show both pro- and anti-inflammatory properties and the balance between omega-3/-6 is considered critical for maintenance of healthy levels of fat (12).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from complement, fatty acids are involved in immunological processes via direct activation of immune cells and release of pro-inflammatory mediators (59). Whereas saturated fatty acids contribute to promoting inflammation, unsaturated fatty acids show both pro- and anti-inflammatory properties and the balance between omega-3/-6 is considered critical for maintenance of healthy levels of fat (12).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies have shown that high‐fat diets (HFDs) and diet‐induced obesity (DIO) serve as tumor promoters resulting in earlier appearance, greater frequency, accelerated growth, larger tumor size, and, in some cases, more frequent metastasis of genetically initiated tumors. These genetic alterations may develop spontaneously and/or be acquired hereditarily, they may be induced by DNA‐damaging agents or they may be created by genetic manipulation . For example, the Min (multiple intestinal neoplastic) mutation, resulting in a truncation mutation in the mouse adenomatous polyposis coli ( Apc ) gene, provides a model for both the human hereditary condition familial adenomatous polyposis and for sporadic colon cancer in humans, where the gene is commonly mutated at an early time in tumor development .…”
Section: Murine Models Obesity and Cancermentioning
confidence: 99%
“…Fatty acids affecting intestinal cancer can be divided into two groups, those that promote colon neoplasia, including medium‐chain saturated fatty acids and lauric and myristic acids; long‐chain saturated fatty acids and palmitic and stearic acids; and ω6 polyunsaturated fatty acids (PUFA) and linoleic and arachadonic acids, all of which have proinflammatory, tumor‐promoting effects as their mechanism of increasing colon cancer risk, enhancing colon cancer development, and increasing mortality. In contrast, unsaturated fatty acids such as oleic and conjugated linoleic acids and ω3 PUFAs including eicosapentaenoic, docosahexaenoic (DHA), and linolenic acids all have anti‐inflammatory properties, function as tumor suppressors, and reduce tumor incidence and growth in mice predisposed to neoplasia owing to either genetic alteration or mutagen exposure . These same principles apply to NAFLD, where hepatocyte lipotoxicity is associated with saturated fatty acids but not with monounsaturated fatty acids, with the effects of the former mediated through activation of lysosomal permeabilization associated with mitochondrial damage, endoplasmic reticulum stress, and activation of apoptosis …”
Section: Dietary Fats and Cancermentioning
confidence: 99%
“…Diet is one of the most important environmental factors representing 25%–30% of all risk factors contributing to cancer development (Ruiz & Hernández, 2014). Several animal model studies have shown the HFD‐induced onset of obesity and the subsequent risk of cancer development (Beyaz et al, 2016; Chen et al, 2016; Doerner & Berger, 2013; Hu et al, 2018; Makowski et al, 2014; Olivo‐Marston et al, 2014). In ovarian cancer, Makowski et al reported that HFD‐mediated obesity promoting ovarian cancer development in KpB mouse was associated with some alterations in genomic and metabolic biomarkers (Makowski et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have previously found that leptin‐promoted ovarian cancer was accompanied with the overexpression of NF‐κB and TNFα (Ghasemi et al, 2017). In animal model studies, HFD have been demonstrated to show stimulatory effects on inflammation via the overexpression of NF‐κB and its downstream targets in various cancer types including prostate (Vykhovanets, Shankar, Vykhovanets, Shukla, & Gupta, 2011), hepatocellular carcinoma (Hill‐Baskin et al, 2009), intestinal neoplasia (Doerner & Berger, 2013), and pancreatic cancer (Murtaugh, 2014).…”
Section: Discussionmentioning
confidence: 99%